Shaping Resilient Futures: The Effect of PAI-Based Anti-Drug Learning Devices in Riau Province's Junior High Schools - Musa Thahir; Munzir Hitami; Zaitun Zaitun (STAI Hubbulwathan Duri, 2023)
This study investigates the impact of using anti-drug learning tools based on Islamic Religious Education (PAI) in Junior High Schools in Riau Province. Through a quasi-experimental research design, two groups of students, namely the experimental group who received PAI-based anti-drug learning tools and the control group who did not receive similar treatment, were compared to measure changes in their understanding of the dangers of drugs, attitudes towards drugs, and strengthening of values. religion. Based on the results of a questionnaire distributed to 7 (seven) State Middle Schools in Riau Province, an average percentage of 74,504% was obtained in the